2020
DOI: 10.1016/j.seizure.2020.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and effectiveness of teleconsultation in children with epilepsy amidst the ongoing COVID-19 pandemic in a resource-limited country

Abstract: The ongoing COVID-19 pandemic and the lockdown measures employed by the government have forced neurologists across the world to look upon telemedicine as the only feasible and practical option to continue providing health care towards children with epilepsy in home isolation. Children with epilepsy are challenging for teleconsultation as direct information from the patient is missing, regarding seizures and adverse effects, especially behavioral and psychological side effects. Methods: Clinical and epilepsy-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(87 citation statements)
references
References 23 publications
3
80
0
4
Order By: Relevance
“…One observational comparative study confirmed that PWE showed more psychological distress than healthy controls, and they spent significantly more time following the COVID-19 outbreak news [13]. Finally, four studies showed that telemedicine may improve access to specialized care for PWE in these difficult times [10,[20][21][22]. The development of an epilepsy electronic patient portal may promote improved patient-clinician partnerships and facilitate patient self-management [23] 1.2.…”
Section: Resultsmentioning
confidence: 99%
“…One observational comparative study confirmed that PWE showed more psychological distress than healthy controls, and they spent significantly more time following the COVID-19 outbreak news [13]. Finally, four studies showed that telemedicine may improve access to specialized care for PWE in these difficult times [10,[20][21][22]. The development of an epilepsy electronic patient portal may promote improved patient-clinician partnerships and facilitate patient self-management [23] 1.2.…”
Section: Resultsmentioning
confidence: 99%
“…Despite all these issues, this is the first systematic review regarding neurological complications of COVID-19 in children and hence is likely to be informative to pediatricians treating these children in providing a comprehensive overview. With the reporting of more children with various neurological complications, precise information regarding the treatment, semiology of seizure, EEG and MRI brain finding and long-term prognosis is likely to be revealed [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there is quick advancement of scope and usage of telemedicine in the field of neurology, also referred to as teleneurology. Beginning with acute stroke care, it is fast expanding to the care of persons with multiple sclerosis, Parkinson’s disease, and epilepsy[ [2] , [3] , [4] , [5] , [6] ]. The two key factors driving the ever-increasing demand for telemedicine in Neurology are limited access to specialists (Neurologists) and difficulties faced by these patients while attending for face-to-face consultation[ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Beginning with acute stroke care, it is fast expanding to the care of persons with multiple sclerosis, Parkinson’s disease, and epilepsy[ [2] , [3] , [4] , [5] , [6] ]. The two key factors driving the ever-increasing demand for telemedicine in Neurology are limited access to specialists (Neurologists) and difficulties faced by these patients while attending for face-to-face consultation[ 6 ]. As there are few pediatric neurologists in India and they are only available in large cities, most of the caregivers face a long waiting time, have to travel a large distance, face a lot of logistic difficulties, and often a lot of financial hardship also.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation